KOMPLEKSITAS MASALAH TINDAK PIDANA KORUPSI PEJABAT KEPALA DAERAH DAN UPAYA PENANGGULANGAN DALAM MEWUJUDKAN PENYELENGGARAAN NEGARA YANG BERSIH DAN BEBAS DARI KORUPSI, KOLUSI DAN NEPOTISME - Sudaryanto, Agus (Jurnal Konstitusi, 2011)
Regulations organizing policies on corruption criminal action and on its enforcement have  long been issued, but this criminal action in general or among the local head officials has increased and extended. This condition prevails since corruption is not only a matter of criminal law and of law enforcement, but also the complexity of the problems surrounding the corruption criminal law. Therefore, any efforts to  cope with this problems should be made integrally by “symptomatical cure”, namely, take action against anybody involved in the action, accompanied with “causative cure”, namely handling and  coping with the complexity of the problems surrounding the corruption criminal law. Then in realizing the state officials who are clean and free from corruption, collusion and nepotism., they should be provided with “code of conduct”, accompanied with clear sanctions (discipline, administrative, and criminal)  according to prevailing laws.